2023
DOI: 10.1021/acs.jctc.2c01092
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Quantitative Information at Quantum Mechanical Level from Noncovalent Interaction Index Analyses

Abstract: The noncovalent interaction (NCI) index is nowadays a well-known strategy to detect NCIs in molecular systems. Even though it initially provided only qualitative descriptions, the technique has been recently extended to also extract quantitative information. To accomplish this task, integrals of powers of the electron distribution were considered, with the requirement that the overall electron density can be clearly decomposed as sum of distinct fragment contributions to enable the definition of the (noncovale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Among many, it is worth highlighting: (i) its extension through the NCI-Milano version to also consider experimental electron densities resulting from multipole model or maximum entropy refinements (Saleh et al, 2012(Saleh et al, , 2013; (ii) the coupling with the ELMO libraries to perform NCI-index analyses based on quantum mechanically rigorous electron density distributions also in the case of large biomolecular systems (Arias-Olivares et al, 2019); (iii) the introduction of more advanced variants of the approach to also obtain quantitative results from the NCIindex computations (see Fig. 10) (Peccati, 2020;Boto et al, 2020;Wieduwilt et al, 2023); (iv) and the creation of a userfriendly webserver to facilitate the analyses of noncovalent interactions in large systems of biological interest (Novoa et al, 2023). Based on the current state-of-the-art, today the NCI-index approach can be considered as a quite mature technique and more and more applications to quantum crystallographic problems are expected in the next years.…”
Section: Advances In Quantum Chemical Topological Approachesmentioning
confidence: 99%
“…Among many, it is worth highlighting: (i) its extension through the NCI-Milano version to also consider experimental electron densities resulting from multipole model or maximum entropy refinements (Saleh et al, 2012(Saleh et al, , 2013; (ii) the coupling with the ELMO libraries to perform NCI-index analyses based on quantum mechanically rigorous electron density distributions also in the case of large biomolecular systems (Arias-Olivares et al, 2019); (iii) the introduction of more advanced variants of the approach to also obtain quantitative results from the NCIindex computations (see Fig. 10) (Peccati, 2020;Boto et al, 2020;Wieduwilt et al, 2023); (iv) and the creation of a userfriendly webserver to facilitate the analyses of noncovalent interactions in large systems of biological interest (Novoa et al, 2023). Based on the current state-of-the-art, today the NCI-index approach can be considered as a quite mature technique and more and more applications to quantum crystallographic problems are expected in the next years.…”
Section: Advances In Quantum Chemical Topological Approachesmentioning
confidence: 99%
“…Nevertheless, charged residues lead to stronger interactions, which are reflected on the distances and hence on the densities . This functionality is to be extended in the future through the use of localized molecular orbitals derived from charged fragments. , …”
Section: Introductionmentioning
confidence: 99%
“…It does not require any a priori parametrization or definition of particular NCIs (i.e., it does not require any notion of what types of interactions are present). Although the NCI index does not provide interaction energies, it has been shown that the integral of the density in the NCI regions are proportional to the strength of the interactions. ,, Thus, it can provide complementary information for the visualization, identification and monitoring of NCIs in such systems. Hence, they have also been included in NCIWEB (see the section entitled “The NCIWEB Server”).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations